Article: ‘Not Everything that Counts Can Be Counted’: The Flaws of the EU Rules on ESG Information - Salerno, Francesco (European company law, 2025)
The EU has introduced various ESG information obligations for large companies and financial intermediaries, hoping to indirectly promote virtuous behaviour. The legislation is spread across a multiplicity of regulatory sources and concerns heterogeneous matters: investor protection and consumer preferences (the SFDR, Delegated Regulation under MIFID II, Listing Act, and Green Claims Directive), disclosure obligations (the NFRD and subsequently Corporate Sustainability Reporting Directive (CSRD)), and company duties (the Taxonomy Regulation and, more recently, Corporate Sustainability Due Diligence Directive (CSDDD)). However, transparency in ESG policies is much more difficult to achieve than in financial information, given the descriptive nature of sustainability information and the lack of standards and well-established operating practices. Comparing the main provisions of European legislation regulating corporate sustainability information, whether mandatory or not, this study aims to show how these provisions are gradually becoming closer to the financial information regime. Despite this, enforcement is weak, because the latter regime is heavily dependent on the choices of individual Member States, which are left to define the system of remedies and sanctions. Perhaps this approach is a compromise, given the differences between the sustainability policies of various national governments, but its transnational nature means that this phenomenon will require a higher level of harmonization.